1994
DOI: 10.1128/aem.60.6.1974-1977.1994
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MK filters for recovery of enteroviruses from tap water

Abstract: The MK filter is an electropositively charged filter that can be used to concentrate enteroviruses from large volumes (400 to 1,000 liters) of water. This filter is less expensive than the commonly used lMDS electropositive filter. In this study, we compared the recovery of poliovirus 1 (PVI) and that of coxsackievirus B3 (CB3) from 378 liters of tap water, using both the MK and the lMDS filters. Viruses were eluted from the filters with 3% beef extract buffered with 0.05 M glycine (pH 9.5) and reconcentrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…was required. The recovery of seeded virus in our protocol was higher than that reported by Chang et al (1981) (50%, using Zeta Plus filters) while comparable to that reported by Ma et al (1994) (c. 90%, using 1MDS filters). Thus, the two-step method of virus concentration developed was rapid, efficient and cost-effective.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…was required. The recovery of seeded virus in our protocol was higher than that reported by Chang et al (1981) (50%, using Zeta Plus filters) while comparable to that reported by Ma et al (1994) (c. 90%, using 1MDS filters). Thus, the two-step method of virus concentration developed was rapid, efficient and cost-effective.…”
Section: Discussionsupporting
confidence: 58%
“…Wallis carried out pioneering work for concentration of viruses in 1960s (Wallis and Melnick 1967a,b;Wallis et al 1969). Different types of matrix materials have been used over the span of fifty years, ranging from gauze pads and glass powder (Bosch et al 1988;Gajardo et al 1991), electronegative membranes (Katayama et al 2002;Lambertini et al 2008) and electropositive cartridges (Sobsey and Glass 1980;Ma et al 1994). Positively charged microporous filters have definite advantage over negatively charged filters as they eliminate the need of water conditioning (acidification and multivalent cation addition) prior to filtration.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used techniques are based on virus adsorption and elution, ultrafiltration and flocculation (Bosch et al 2008). These techniques show various efficiencies of recovery (between 20 and 95%) according to the structure and physico-chemical properties of viruses (Rose et al 1984;Ma et al 1994;Enriquez and Gerba 1995;Katayama et al 2002;Lambertini et al 2008;Girones et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Virus detection requires an efficient concentration step from a large volume of water to a much smaller volume. Several concentration methods have been already developed including the adsorption of viruses on cartridges, membranes or glass wool by electrostatic interactions followed by their elution in a small volume (Rose et al 1984;Ma et al 1994;Enriquez and Gerba 1995;Katayama et al 2002;Lambertini et al 2008) or the ultrafiltration technique (Hill et al 2009;Polaczyk et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Sedmak et al, 2005). A different electropositive material (MK) is cheaper but its recoveries were reported to be not as good as 1 MDS in comparative tests (Ma et al, 1994). Improvements to poliovirus and norovirus recovery from tap water samples by coating of electropositive Zetapor filters by passage of AlCl 3 prior to filtration was reported by Haramoto et al (2004).…”
Section: Adsorption To Electropositive Membranes and Cartridgesmentioning
confidence: 99%